2019
DOI: 10.1152/ajpcell.00142.2018
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-150 suppresses epithelial-mesenchymal transition, invasion, and metastasis in prostate cancer through the TRPM4-mediated β-catenin signaling pathway

Abstract: Prostate cancer (PCa) remains one of the leading causes of cancer-related deaths among males. The aim of the current study was to investigate the ability of microRNA-150 (miR-150) targeting transient receptor potential melastatin 4 (TRPM4) to mediate epithelial-mesenchymal transition (EMT), invasion, and metastasis through the β-catenin signaling pathway in PCa. Microarray analysis was performed to identify PCa-related differentially expressed genes, after which both the mirDIP and TargetScan databases were em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…Transient receptor potential melastatin‐4 knockout cells were characterized by lower viability, lower proliferation, and a cell cycle shift to G1 phase (Figs and ). These findings are in line with data from PCa cells (Hong and Yu, ), as TRPM4 inhibition by microRNA‐150 regulates cell cycle and proliferation via a cell cycle shift toward G1. Additionally, Ricardo Armisén’s group demonstrated that TRPM4 regulates cell cycle progression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Transient receptor potential melastatin‐4 knockout cells were characterized by lower viability, lower proliferation, and a cell cycle shift to G1 phase (Figs and ). These findings are in line with data from PCa cells (Hong and Yu, ), as TRPM4 inhibition by microRNA‐150 regulates cell cycle and proliferation via a cell cycle shift toward G1. Additionally, Ricardo Armisén’s group demonstrated that TRPM4 regulates cell cycle progression.…”
Section: Discussionsupporting
confidence: 90%
“…Transient receptor potential melastatin‐4 channel (TRPM4) is expressed in several human tissues (Launay et al , ; Nilius et al , ) and has been identified as a cancer driver gene that contributes to migration, proliferation, and invasion of prostate cancer (PCa) cells (Berg et al , ; Holzmann et al , ; Sagredo et al , , ; Schinke et al , ). In PCa, TRPM4 expression is negatively regulated by microRNA‐150, which results in a shift in cell cycle to G1 phase (Hong and Yu, ). The mechanism of TRPM4’s contribution to PCa hallmark functions remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…According to these findings, miR-150-5p inhibits the expression of TRPM4, a gene known to promote the activation of the Wnt/β-catenin signaling (associated with tumorigenesis), and the cell-cycle progression and cell proliferation in several PCa cell lines. Moreover, the upregulation of miR-150-5p and the downregulation of TRPM4 promotes apoptosis and suppresses epithelial–mesenchymal transition, cell migration, invasion, and metastasis by repressing β-catenin signaling [20].…”
Section: Discussionmentioning
confidence: 99%
“…miR-150 directly targets the TRPM4 gene and suppresses TRPM4 expression in PCa tissues (93). Upregulation of miR-150 or silencing of TRPM4 suppresses EMT phenotypes, migration and invasion, leading to inhibition of metastasis (93). In an independent study with PC3 cells, silencing of TRPM4 decreased the expression of Snail1, an EMT transcription factor, and also multiple representative EMT markers, thus inhibiting cell migration and invasion and validating the TRPM4-mediated regulation of migration and invasion (94).…”
Section: Trp Channels In Prostate Cancermentioning
confidence: 94%
“…Silencing of TRPM4 reduces cell migration, but does not affect the growth of PC3 and DU145 cells, which are androgennonresponsive prostate cancer cell lines (92). miR-150 directly targets the TRPM4 gene and suppresses TRPM4 expression in PCa tissues (93). Upregulation of miR-150 or silencing of TRPM4 suppresses EMT phenotypes, migration and invasion, leading to inhibition of metastasis (93).…”
Section: Trp Channels In Prostate Cancermentioning
confidence: 99%